Disaster Risk and Property Valuation: : A Study of Auction Assets in Earthquake-Prone Yogyakarta - Rahmat Saleh; Asmara, Gea Dwi; Wulandari, Nurafifah (REGION, 2026)
This study aims to determine and identify the effects of property characteristics including exposure time, elevation adjustment, and topographic adjustment and disaster characteristics, such as seismicity, on the value of auctioned assets (collateral). The research employs multiple regression analysis using the ordinary least squares method. The findings indicate that property characteristics, including elevation, topography, exposure time, and seismicity-related disaster characteristics, significantly affect the value of auctioned assets. Specifically, the Topography and Seismic Adjustment variables have a positive and significant influence on the Auction Market Value of collateral property assets. This research introduces a novel approach to understanding asset auction dynamics in earthquake-affected areas by integrating economic valuation with disaster analysis. The study's originality lies in combining an economic analysis framework with disaster risk factors, an area seldom emphasized in previous asset auction research, which has typically addressed economic valuation and disaster impacts separately.